Performance of the large scale HV-CMOS pixel sensor MuPix8 - Augustin, Heiko; Berger, Niklaus; Blattgerste, Christoph; Dittmeier, Sebastian; Ehrler, F.; Grzesik, C.; Hammerich, Jan; Herkert, Adrian; Huth, Lennart; Immig, David; Kozlinskiy, A.; Köppel, M.; et al. (Journal of Instrumentation, 2019)
The Mu3e experiment is searching for the charged lepton flavour violating decay\break μ+→ e+ e− e+, aiming for an ultimate sensitivity of one in 1016 decays. In an environment of up to 109 muon decays per second the detector needs to provide precise vertex, time and momentum information to suppress accidental and physics background. The detector consists of cylindrical layers of 50 μm thin High Voltage Monolithic Active Pixel Sensors (HV-MAPS) placed in a 1 T magnetic field. The measurement of the trajectories of the decay particles allows for a precise vertex and momentum reconstruction. Additional layers of fast scintillating fibre and tile detectors provide sub-nanosecond time resolution. The MuPix8 chip is the first large scale prototype, proving the scalability of the HV-MAPS technology. It is produced in the AMS aH18 180 nm HV-CMOS process. It consists of three sub-matrices, each providing an untriggered datastream of more than 10 MHits/s. The latest results from laboratory and testbeam characterisation are presented, showing an excellent performance with efficiencies >99.6 % and a time resolution better than 10 ns achieved with time walk correction.